2020
DOI: 10.1186/s12935-019-1085-6
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 correlates with immune and clinical characteristics of glioma

Abstract: Background: CTLA-4 is a well-studied immune checkpoint protein that negatively regulates T cell-mediated immune responses. However, the expression of CTLA-4 in glioma and the effects of CTLA-4 on prognosis in patients with glioma have not yet been examined. Methods: We investigated the protein level of CTLA-4 in human glioma samples, extracted genetic and clinical data from 1024 glioma patients to characterize CTLA-4 expression and its relationship with immune functions in gliomas. R language was used for stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 42 publications
4
94
1
Order By: Relevance
“…CTLA4 negatively regulates T cell activation by blocking the function of costimulatory signal and differentiation cluster CD28:B7 binding (35). CTLA4 inhibitors reverse inhibitory immune signal and restore the anti-cancer response by blocking the interaction between CTLA4 and the ligand expressed by antigen presenting cells (32). With the approval of CTLA4 inhibitor Ipilimumab for clinical applications, it has been used for metastatic melanoma after the rst-line treatment (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTLA4 negatively regulates T cell activation by blocking the function of costimulatory signal and differentiation cluster CD28:B7 binding (35). CTLA4 inhibitors reverse inhibitory immune signal and restore the anti-cancer response by blocking the interaction between CTLA4 and the ligand expressed by antigen presenting cells (32). With the approval of CTLA4 inhibitor Ipilimumab for clinical applications, it has been used for metastatic melanoma after the rst-line treatment (14).…”
Section: Discussionmentioning
confidence: 99%
“…D Planchard et al reported that combination immunotherapy of PD-L1 and CTLA4 considerably prolonged the OS in advanced refractory colorectal cancer (31). Combination immunotherapy tends to replace monotherapy, for that the combinational usage of ICBs can produce higher synergistic anti-tumor e ciency and reduce side effects (32). Therefore, we continued to explore the correlation between CTLA4 and other immune checkpoint molecules, including PDCD1 (PD-1), CD274 (PD-L1), LAG3, indoleamine-2,3-dioxygenase-1 (IDO1), and TIGIT (33) (34).…”
Section: Ctla4 Was Highly Related To Other Immune Checkpoint Moleculesmentioning
confidence: 99%
“…Differential expression of 7 established immune checkpoint genes in the low and high-risk groups was analyzed. These are, T cell immunoglobulin domain and mucin domain 3 (TIM3), programmed cell death 1 (PD1), PD1 interacts with programmed death ligand 1 (PDL1), cytotoxic T lymphocyte antigen 4 (CTLA4), T cell immunoreceptor with Ig and ITIM domains (TIGIT), long non-coding RNA MIR 155 host gene (MIR155HG), and CD48 [20][21][22][23][24] . This analysis evaluated the correlation between risk score and expression of the checkpoint genes.…”
Section: Analysis Of Correlation Between Risk Score and Expression Ofmentioning
confidence: 99%
“…CTLA4 negatively regulated T cell activation by blocking the function of costimulatory signal and differentiation cluster CD28: B7 binding (33). CTLA4 inhibitors reverse the inhibitory immune signal and restore the anti-cancer response by blocking the interaction between CTLA4 and the ligand expressed by antigen presenting cells (30). With approval of CTLA4 inhibitor Ipilimumab for clinical applications, it has been used for metastatic melanoma after the rst-line treatment (13).…”
Section: Discussionmentioning
confidence: 99%
“…D Planchard et al reported that combination immunotherapy of PD-L1 and CTLA4 considerably prolonged the OS in advanced refractory colorectal cancer (29). Combination immunotherapy tends to replace monotherapy, for that the combinational usage of ICBs can produce higher synergistic anti-tumor e ciency and reduce side effects (30). Therefore, we continued to explore the correlation between CTLA4 and other immune checkpoint molecules, including PDCD1 (PD-1), CD274 (PD-L1), LAG3, indoleamine-2,3-dioxygenase-1 (IDO1), and TIGIT (31) (32).…”
Section: Ctla4 Was Highly Related To Other Immune Checkpoint Moleculesmentioning
confidence: 99%